Shifting towards active and sustainable commuting: the relative importance of factors associated with reduced car commuting among Finnish public sector employees - Jussila, Juuso J.; Gluschkoff, Kia; Halonen, Jaana I.; Kurkela, Olli; Lanki, Timo; Makkonen, Anna; Rehunen, Antti; Salo, Paula; Suomalainen, Emilia; Tainio, Marko; Ervasti, Jenni (Elsevier BV, 2026)
Shifting from car to walking, cycling, or public transport increases physical activity and decreases traffic-related emissions. However, many commutes with healthier transportation options are still undertaken by private cars, highlighting the need for a deeper understanding of the factors associated with commuting modal shift. By linking individual-level survey data with grid-based data on the residential environment, we examined the relative importance of factors associated with reduced car commuting from 2020 to 2022 among 4464 Finnish public sector employees using dominance analysis. While the overall predictive power of the analysis was low, shorter average commute length, lower proportion of green areas, being a non-smoker, higher proportion of households without a car, shorter distance to the nearest grocery shop, less car ownership, higher total physical activity, and lower body mass index emerged as the most important factors. Results suggest that residential environment, health, and health behaviours only explain a small proportion of the total variance in a shift towards healthier commuting. Future studies should explore the role of individual psychosocial factors and workplace environment characteristics in explaining modal shifts in commuting within Nordic countries.